2023
DOI: 10.1042/bst20220434
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of amyloid β aggregates with phospholipid membranes and the implications for neurodegeneration

Abstract: Misfolding, aggregation and accumulation of Amyloid-β peptides (Aβ) in neuronal tissue and extracellular matrix are hallmark features of Alzheimer's disease (AD) pathology. Soluble Aβ oligomers are involved in neuronal toxicity by interacting with the lipid membrane, compromising its integrity, and affecting the function of receptors. These facts indicate that the interaction between Aβ oligomers and cell membranes may be one of the central molecular level factors responsible for the onset of neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Although numerous studies have identified CP interactions (Infield et al, 2021) between proteins and membranes, to our knowledge, there has been no previous study of AQ interactions between the lipid bilayer and integral membrane proteins. The combined observations of AQ in fibrils and membranes could also facilitate the comprehension of interactions of amyloid aggregates with phospholipid membranes in neurodegeneration (Budvytyte & Valincius, 2023). In addition, several examples show that AQcalc, with the availability of AF2 models, can facilitate fine structural characterization of the impact of PTMs (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have identified CP interactions (Infield et al, 2021) between proteins and membranes, to our knowledge, there has been no previous study of AQ interactions between the lipid bilayer and integral membrane proteins. The combined observations of AQ in fibrils and membranes could also facilitate the comprehension of interactions of amyloid aggregates with phospholipid membranes in neurodegeneration (Budvytyte & Valincius, 2023). In addition, several examples show that AQcalc, with the availability of AF2 models, can facilitate fine structural characterization of the impact of PTMs (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical heterogeneity and unclear pharmacodynamics characterise non-peptidic anti-aggregants investigated to date. Anti-aggregants may function by attaching to Aβ monomers, blocking oligomerization and facilitating elimination; Substances with high CNS bioavailability, low immunogenicity, and low toxicity are diificult to find ( RimaBudvytyte and GintarasValincius, 2023 ).…”
Section: Drug Therapymentioning
confidence: 99%
“…The Aβ42 sequence consists of hydrophilic, charged, N-terminal residues 1-16; the central hydrophobic core (CHC, residues 17-21); a hydrophilic region (residues [22][23][24][25][26][27][28] and hydrophobic residues 30-42. Numerous studies have reported that low-molecular-weight (LMW) oligomers of Aβ generated during the lag phase of aggregation or released from the fibrils are the key players in AD [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments also showed that ganglioside-enriched vesicles promoted Aβ oligomerization and disruption of the membrane [26]. The impact of metal ions or lipid vesicles on Aβ aggregation has been studied [2,27,28]; their combined effects are not well understood. It was shown, however, that the co-effect of Cu 2+ and lipid vesicles led to the rapid formation of abundant Aβ40 LMW oligomers containing β-sheet-rich structures [29].…”
Section: Introductionmentioning
confidence: 99%